2002
DOI: 10.1159/000066478
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Outcome of Sleep Apnoea in PWS during the Initial Phase of Growth Hormone Treatment

Abstract: The case of a boy with Prader-Willi syndrome (PWS) who suffered from respiratory problems since birth and suddenly died at the age of 6.5 years, 4 months after initiation of GH therapy, is presented. This case indicates the possibility of fatal courses in infants and children with PWS as a consequence of respiratory problems and raises the question as to a causal connection between the initiation of GH therapy and the sudden death of this child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 16 publications
3
52
0
2
Order By: Relevance
“…49 Concern about the possible contribution of GH administration to unexpected death has been raised by reported deaths of individuals within a few months of starting GH therapy. [50][51][52][53][54][55] The few reported deaths were mostly in obese individuals who had preexisting respiratory or cardiac disorders with evidence of upper airway obstruction and uncorrected tonsillar and adenoidal hypertrophy. In the database of one pharmaceutical company, five of 675 children treated with GH died suddenly of respiratory problems.…”
Section: Hypogonadismmentioning
confidence: 99%
“…49 Concern about the possible contribution of GH administration to unexpected death has been raised by reported deaths of individuals within a few months of starting GH therapy. [50][51][52][53][54][55] The few reported deaths were mostly in obese individuals who had preexisting respiratory or cardiac disorders with evidence of upper airway obstruction and uncorrected tonsillar and adenoidal hypertrophy. In the database of one pharmaceutical company, five of 675 children treated with GH died suddenly of respiratory problems.…”
Section: Hypogonadismmentioning
confidence: 99%
“…Existem alguns relatos de caso de morte súbita em pacientes portadores de SPW após início da terapia de reposição com GH (28)(29)(30)(31). Em razão disso, foram realizados estudos com a finalidade de elucidar o…”
Section: Hormônio De Crescimento (Gh)unclassified
“…However, there are some concerns regarding the risks involved in GH treatment of PWS patients. First, there was a report of sudden death owing to the use of GH treatment [12]. Although the relationship between the sudden death and GH treatment was completely unclear, Nagai et al [13] subsequently reported that the causes of sudden unexpected death did not differ between PWS patients with or without GH treatment.…”
Section: Discussionmentioning
confidence: 99%